Reaction of native fruit trees from brazilian Amazon to Meloidogyne enterolobii - De Almeida, Eduardo José; Dos Santos, Jaime Maia; Martins, Antonio Baldo Geraldo; Alves, Gleina Costa Santos (My University, 2011)
This research was conducted in a greenhouse from Department of Fitossanity at São Paulo State University, Jaboticabal, SP, to evaluate the reaction of four Amazon's native fruits tree species [Abiu (Pouteria caimito), Araça Pera (Psidium acutangulum ), Camu-camu (Myrciaria dubia) and Bacuri (Platonia insignis )] and one from Central America, Sapodilla (Achras zapota) to the root-knot nematode Meloidogyne enterolobii Yang & Eisenback, 1983 (Meloidogynidae: Heteroderidae). Seedlings of each fruit trees averaging 12 months of age were planted in ceramic pots containing autoclaved soil and sand. They were inoculated, with addition of 10 cm3 of 400 eggs and J2 in suspension per cm3 to the root system, with a total initial population (IP) of 4000 eggs and J2 of M. enterolobii. The nematode population was obtained from roots of guava tree (Psidium guajava) in the city of Vista Alegre do Alto, SP. The assessment was carried out after 150 days at inoculation with the recovery and counting of the final nematode population (FP) in the root system of the fruit trees. The reaction of the fruit species was given by the factor of nematode reproduction (RF) according to the equation FP / IP, where RF > 1 was considered susceptible and RF < 1, resistant. The Araça Pera was susceptible to M. enterolobii and the others fruits plant were not favorable host to M. enterolobii. This study reports the first infection in P. acutangulum by M. enterolobii in greenhouse conditions.
Keywords: Amazon fruit trees; Reproduction factor; Resistance; Root-knot